2021
DOI: 10.1016/j.adolescence.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining a new prosocial risk‐taking scale in a longitudinal sample of ethnically diverse adolescents

Abstract: Introduction This longitudinal study designed and tested the validity of a new measure of prosocial risk taking — risks that individuals take in order to help others. Methods The sample was racially and ethnically diverse adolescents in the rural Southeastern United States (N = 867; Mage = 12.82 years, 10–14 years at Wave 1; 50% Girls, 33% White non‐Latinx, 27% Latinx, 20% Black, 20% Mixed/Other race/ethnicity). Adolescents completed self‐report measures of the new prosocial risk‐taking scale at baseline and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We also did not measure prosocial risk‐taking (such as speaking up to defend a friend), or the motivations behind the risk‐taking behaviors we did measure (such as stealing in order to help a friend). Daily diary items for these prosocial risk‐taking behaviors and others (Armstrong‐Carter, Do, Guassi Moreira, Prinstein, & Telzer, 2021; Do et al., 2017) may shed further light on the daily connection between risk‐taking and prosocial behavior during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not measure prosocial risk‐taking (such as speaking up to defend a friend), or the motivations behind the risk‐taking behaviors we did measure (such as stealing in order to help a friend). Daily diary items for these prosocial risk‐taking behaviors and others (Armstrong‐Carter, Do, Guassi Moreira, Prinstein, & Telzer, 2021; Do et al., 2017) may shed further light on the daily connection between risk‐taking and prosocial behavior during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adolescents show incredible kindness by helping and comforting their peers, family, and strangers in distress (Andrew, 2018). Some recent studies have reported that adolescents demonstrate a remarkable capacity to help others -prosocial risk-taking, and they may do so even when it involves personal risk to their benefits, such as financial, health, academic, or social reputational loss (Do et al, 2017;Blankenstein et al, 2020;Armstrong-Carter et al, 2021). Various studies support the hypothesis that prosocial behavior is linked to an increase in social risk tolerance during adolescence.…”
Section: Individuals Generally Show An Obvious Altruistic Risk-seekin...mentioning
confidence: 98%
“…Various studies support the hypothesis that prosocial behavior is linked to an increase in social risk tolerance during adolescence. For example, Armstrong-Carter et al (2021) found that older adolescents demonstrated increased levels of prosocial tendencies during the years when they were more tolerant of social risk. Furthermore, increased risk levels of both personal cost (Experiment 1) and the failure to help others (Experiment 2) weaken altruistic risk-seeking tendencies.…”
Section: Individuals Generally Show An Obvious Altruistic Risk-seekin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Armstrong‐Carter et al. recently developed a prosocial risk taking scale, though it is intended for use with adolescents (Armstrong‐Carter et al., 2021). Wood et al.…”
Section: Introductionmentioning
confidence: 99%